Traditional Chinese medicine powder for improving egg yield of pavo critatus - YANG LIJUAN; YU WEI; MA XIAOFEI (2017)
The invention discloses traditional Chinese medicine powder for improving the egg yield of pavo critatus. The traditional Chinese medicine powder is prepared from, by weight, Chinese dodder seeds 4-10%, epimedium2-5%, rhizoma anemarrhenae 4-10%, dried tangerine or orange peels 2-5%, hawthorn 4-7%, malt2-10%, pine needles2-10%, caulis tinosporae sinensis 4-10%, royal paulowinia flower2-10% and echinacea 2-8% and is prepared by mixing the raw materials by according to the weight percentage. The traditional Chinese medicine powder has good palatability and high nutrient digestibility, can improve the intestinal microecological balance of the pavo critatus, promote the growth and development of the pavo critatus, improve the annual egg yield of the pavo critatus and prolong the egg laying time of the pavo critatus. 本发明公开种提高蓝孔雀产蛋量的中药散剂，该中药散剂的配方按重量百分比为：菟丝子4～10%、淫羊藿2～5%、知母4～10%、陈皮2～5%、山楂4～7%、麦芽2～10%、松针2～10%、宽筋藤4～10%、泡桐花2～10%、紫锥菊2～8%，由以上重量百分比数的原料混合制成。本发明适口性好，营养物质消化率高，能改善孔雀肠道微生态平衡，促进孔雀生长发育，提高孔雀年产蛋量，延长孔雀的产蛋时间。